2014
DOI: 10.1002/jgt.21784
|View full text |Cite
|
Sign up to set email alerts
|

Degree Conditions for Spanning Brooms

Abstract: A broom is a tree obtained by subdividing one edge of the star an arbitrary number of times. In (E. Flandrin, T. Kaiser, R. Kužel, H. Li and Z. Ryjáček, Neighborhood Unions and Extremal Spanning Trees, Discrete Math 308 (2008), 2343–2350) Flandrin et al. posed the problem of determining degree conditions that ensure a connected graph G contains a spanning tree that is a broom. In this article, we give one solution to this problem by demonstrating that if G is a connected graph of order n≥56 with δ(G)≥n−23, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Further, the results in this article can be used to give conditions whether a graph contains a k-balanced tree or a k-comet as a spanning tree. Research concerning this and similar questions can be found, for example, in the work of Flandrin et al [5] and Chen et al [4].…”
Section: Introductionmentioning
confidence: 87%
“…Further, the results in this article can be used to give conditions whether a graph contains a k-balanced tree or a k-comet as a spanning tree. Research concerning this and similar questions can be found, for example, in the work of Flandrin et al [5] and Chen et al [4].…”
Section: Introductionmentioning
confidence: 87%
“…A spanning tree with at most one branch vertex is called a spider. Gargano, Hammar, Hell, Stacho and Vaccaro [15] (also see Gargano and Hammar [14]) proved that if G is a connected graph on n vertices with δ(G) ≥ (n − 1)/3, then G contains a spanning spider (Later Chen, Ferrara, Hu, Jacobson and Liu [6] proved the stronger result that connected graphs on n ≥ 56 vertices with δ(G) ≥ (n − 2)/3 contain a spanning broom; that is, a spanning spider obtained by joining the center of a star to an endpoint of a path). Motivated by this, Gargano et al [15] conjectured that for all s ≥ 1, if G is a connected graph on n vertices with δ(G) ≥ (n − 1)/(s + 2), then G contains a spanning tree with at most s branch vertices.…”
Section: Introductionmentioning
confidence: 99%
“…There has been much recent work on conditions implying particular structural properties in spanning trees. See for example , , or the recent survey by Ozeki and Yamashita on spanning trees.…”
Section: Introductionmentioning
confidence: 99%